2017
DOI: 10.2147/ppa.s132054
|View full text |Cite
|
Sign up to set email alerts
|

Patient opinions on medicine-use review: exploring an expanding role of community pharmacists

Abstract: BackgroundCurrent evidence supports the benefit of medicine-use review (MUR) for the safe and effective use of medicines. However, little is known about opinions of consumers regarding their preference for undertaking MUR, especially in the developing world, eg, in some Asian countries. We aimed to explore patients’ opinions about potential MUR and other enhanced services provided by community pharmacists.Patients and methodsA qualitative study using focus groups was conducted at Naresuan University’s communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…Patients also need to actively cooperate with the hospital pharmacists. 33 Relevant departments can strengthen education and publicity on the rational use of drugs by patients to improve patients’ sense of responsibility. 34 , 35 The mutual understanding and mutual respect between the hospital pharmacists and patients may be a key point for improving the patients’ medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Patients also need to actively cooperate with the hospital pharmacists. 33 Relevant departments can strengthen education and publicity on the rational use of drugs by patients to improve patients’ sense of responsibility. 34 , 35 The mutual understanding and mutual respect between the hospital pharmacists and patients may be a key point for improving the patients’ medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Young et al [ 13 ] found that pharmacists did not routinely direct patients to medicine information websites and thought leaflets might worry patients about possible side effects. Aimaurai et al [ 14 ] proposed that community pharmacists could offer a Medicines Use Review service to ensure the quality use of medicines in the community after recognizing the unmet needs of patients for information on medicine.…”
Section: Introductionmentioning
confidence: 99%
“…A potential facilitator proposed by our study participants was that they received an invitation for a dMUR from the pharmacist. This has been suggested as a means to increase uptake by others [29]. However, this would need to be facilitated by the routine sharing of discharge communication between the hospital and the community pharmacist.…”
Section: Discussionmentioning
confidence: 99%